Evaluation of Bactericidal Activity of 7-Arylaminoisoquinolin-5,8-Quinones Against Piscirickettsia Salmonis - Valenzuela-Montenegro, B; Ibacache-Rojas, J (John Wiley and Sons Inc, 2023)
[No abstract available]